Design of whole-genome tiling microarrays for staphylococcus aureus NCTC 8325 and pseudomonas aeruginosa PA01 - Tan, Steffe Jie Ing. (2009)
Optimal design of microarray probes has a direct impact on the reliability of microarray results. Since whole genome tiling arrays have vast potential in the biotechnology industry, it is desirable to design reliable tiling probes with good genome coverage. The objective of this project is to design whole-genome tiling microarrays for Staphylococcus aureus NCTC 8325 and Pseudomonas aeruginosa PA01.